6x-2x+7=x-2+9

Simple and best practice solution for 6x-2x+7=x-2+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-2x+7=x-2+9 equation:


Simplifying
6x + -2x + 7 = x + -2 + 9

Reorder the terms:
7 + 6x + -2x = x + -2 + 9

Combine like terms: 6x + -2x = 4x
7 + 4x = x + -2 + 9

Reorder the terms:
7 + 4x = -2 + 9 + x

Combine like terms: -2 + 9 = 7
7 + 4x = 7 + x

Add '-7' to each side of the equation.
7 + -7 + 4x = 7 + -7 + x

Combine like terms: 7 + -7 = 0
0 + 4x = 7 + -7 + x
4x = 7 + -7 + x

Combine like terms: 7 + -7 = 0
4x = 0 + x
4x = x

Solving
4x = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
4x + -1x = x + -1x

Combine like terms: 4x + -1x = 3x
3x = x + -1x

Combine like terms: x + -1x = 0
3x = 0

Divide each side by '3'.
x = 0

Simplifying
x = 0

See similar equations:

| 5x+6=30+x | | 30xm+15xn-20ym-10yn= | | 25x^4-81y^2=0 | | 1/4x=x-33 | | 5-(-3)+6= | | f(x)=-4x^2+16x-5 | | x/(36x^2-9) | | x+2x+5x=32 | | x^2+14xy+24y=0 | | 5+4ln(x)=7 | | x/36x^2-9 | | m^2+22m-4=0 | | y^4-6y^3+12y^2-10y+3= | | a=-1e+-1s+-1y | | w^2-13w+42.25=0 | | 1/4x^4-9/25=0 | | ydx=x(lnx-lny)dy | | 5x=(3x-3)(m+4) | | 0.90n=n+15 | | -17+8x=14 | | 0.75p=18 | | 8x-4x+5=x-5+10 | | 2x+40=9x-2 | | 0=1/3x=1 | | 11r+60=15 | | 8(v+3)-2v=3(2v+4)-18 | | 3(x-8)=x+2 | | a=cx+bc | | 11x-12=5(2x+3)-3 | | 6/27 | | 0.06t+0.09(t+500)=150 | | 2x+17=9x-4 |

Equations solver categories